Effect of technological process on antioxidant capacity and total phenolic content of Andean lupine (Lupinus mutabilis Sweet) - Córdova-Ramos, Javier S. (2020)
The effect of debittering, extrusion and spray drying on antioxidant capacity and total phenolic compounds in non-defatted and defatted flours from three Andean lupine genotypes (Altagracia, Andenes, and Yunguyo) was evaluated. Total phenolic content (TPC; Folin-Ciocalteu method) and antioxidant capacity (DPPH and ABTS+) were assessed by spectrophotometry. Results showed that technological processes decreased significantly (p ≤ 0.05) antioxidants and phenolic compounds. Bitter lupine (control sample) had higher (p ≤ 0.05) TPC and antioxidant capacity than processed samples. In non-defatted and defatted samples, TPC of processed samples varied between 0.64 - 1.10 and 0.75 - 1.33 mg gallic acid equivalent/g d.m. in non-defatted and defatted samples, respectively. The DPPH antioxidant capacity varied between 2.87 - 4.10 and 3.12 - 4.73 μmol Trolox/g d.m., while the ABTS+ antioxidant capacity ranged between 50.65 - 75.56 and 61.63 - 76.88 μmol Trolox/g d.m. in non-defatted and defatted samples, respectively. On the other hand, lipids negatively influenced the quantification of TPC; therefore, the defatted samples had higher TPC.